Extra-clausal constituents in Functional Discourse Grammar: function and form - Giomi, Riccardo; Keizer, Evelien (Revista da ABRALIN, 2020)
This paper presents a first outline of an encompassing account of extra-clausal constituents (ECCs) within the framework of Functional Discourse Grammar (FDG). Drawing primarily on English corpus data, we investigate both the functional and the formal properties of this heterogeneous class of constituents, focusing in particular on their underlying pragmatic structure and contribution to the ongoing discourse, and on the communicative factors relevant to their placement within the larger linguistic expressions within which they occur. More specifically, we suggest that each ECC forms a separate, though invariably dependent unit of communicative behaviour (i.e. a Subsidiary Discourse Act). Moreover, we argue that the mechanism governing the placement of ECCs vis-à-vis both their hosts and each other is fundamentally different from the placement rules proposed in FDG for morphosyntactic units belonging to the clause, phrase or word; the result is a system that captures both the functional constraints on the placement of ECCs and their greater positional freedom.